Determination of the plastic viscosity of superplasticized cement pastes through capillary viscometers. (10th November 2020) - de la Rosa, Ángel; Poveda, Elisa; Ruiz, Gonzalo; Moreno, Rodrigo; Cifuentes, Héctor; Garijo, Lucía
Highlights: 38 fluid cement pastes analyzed by capillary viscometers/rotational rheometer. Marsh funnel's accuracy depends on the type of analysis. Cannon–Fenske viscometer accurately measures η p of fluid cement pastes. Cannon–Fenske viscometer is suitable for the construction industry. Abstract: Determining correctly the rheological parameters of the cement paste is a matter of capital importance when designing a self-compacting concrete (SCC). For this, it is necessary to resort to rheometers, which are expensive and, therefore, not available in all laboratories. However, the measurement of plastic viscosity can also be carried out using capillary viscometers, simple and cheap instruments whose foundation lies in the time it takes for a volume of suspension to flow through the hole in a capillary. It is common practice to use the Marsh funnel in the construction industry but not the Cannon–Fenske viscometer, more used in other industries such as chemistry. Besides, most of the models associated with the Marsh funnel have been developed for drilling muds, although there are some exclusive for cementitious suspensions. However, the rheological nature of both materials is very similar, so it seems appropriate to check how these models behave in cement pastes designed for SCC. Consequently, the rheological behavior of 39 cement pastes of different composition was studied (varying the nature of cementitious materials and the superplasticizer admixture, with various water–cementitious materials ratios) to check the performance of said devices and models using the plastic viscosity measured with a rotational rheometer as a reference. The results indicate that the Cannon–Fenske viscometer offers a better approximation to the reference plastic viscosities than the Marsh funnel. As for the comparison between models for the Marsh funnel, the results obtained are disparate, so it would be convenient to expand the experimental research to adjust the parameters of the models that offer a good approach.